The analogy in the poetry and prose of Ibn Hariq Al Balansi - Ameen , Dunya; Hussain, Muhammed (Humanities Journal of University of Zakho, 2023)
This research implies an exposition about one of the Anadalian Era poets (Ibn Hariq Al- Bilinsy). He was one of the literary men who versed in the notation of poems and prose dissertations..The research includes Ibn Hariq Al _ Bilinsy’s origins; where and when he was born, the reason behind his nickname. Following that, there is a definition of rhetorical simile derived from famous and authentic resources of rhetoric masters such as Al Khatib Al Qizwiny, Abdul Aziz Attiq and Ahmed Matloob. Simile comes with several auxiliaries and terms. Thus, the first chapter includes all sorts of singular and compound simile.So, the singular simile includes elliptic simile, comprehensive simile, eloquent, using poetic and prose texts. Furthermore, compound simile which includes histrionic and implicit simile. The first dissertation of the first chapter clarifies the elliptic simile. Which should have a simile auxiliary, the resimblant, the resembled to and the point of resemblance. Concerning the second chapter, it discusses the histrionic simile which must be within simulating attitudes to one another. It is the simile that springs from the situation. It is also about implicit simile which results from comprehending the context. In conclusion, Ibn Hariq, the poet was one of the bright and wise poets. Through which he rhymed his poems, added to them and enriched the Anadalian literature.